The Linkage between Psychological Capital and Public Service Motivation: Evidence from Taiwan - Jang, Chyi-Lu (Archives of Business Research, 2016)
Research on positive organizational behaviors has demonstrated the potential of psychological capital as a predictor of various workplace outcomes. To examine the relationship between Positive Psychological Capital (PsyCap) (Luthans, Youssef, & Avolio, 2007a) and Public Service Motivation (PSM) (Perry & Wise, 1990), this study uses a questionnaire to survey 311 public servants employed by 5 local governments in Taiwan. Regression analysis results indicate that psychological capital is positively related to all dimensions of PSM. Similarly, our findings also reveal that individuals with high psychological capital report higher levels of PSM than do their low PsyCap counterparts. In summary, positive psychological capital can function as a strong predictor of public service motivation.